Capital Structure and Financial Performance of Listed Brewery Firms in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study investigated the relationship between Capital Structure and Financial Performance of Listed Breweries Companies in Nigeria with the moderating factor of firm size. The study developed five specific objectives, five research questions as well as five hypotheses and used generalized mean, standard deviation and multiple regression with the aid of Statistical Package for Social Sciences (SPSS) to analyze the secondary data extracted from the annual reports and accounts of the companies studied. Data was gathered from secondary sources. Secondary data were sourced from annual reports of the companies available at the Nigerian Exchange Group (websites). Correlational research design was adopted and population of the study consists of five (5) listed breweries companies on the Nigerian Exchange group December 2021. Using census sampling technique, the five companies were selected to constitute the sample for the study. Capital Structure predictor variables were proxied by Equity Financing and debt financing. While Financial Performance criterion variables were measured by return on asset and return on Investment. The study found that capital structure has a positive and insignificant relationship with financial performance of listed brewery companies in Nigeria. Based on the findings, conclusions were reached that Equity financing has a positive, very weak and insignificant effect on Return on and return on investment. Similarly, Debt financing has a positive, very weak and insignificant relationship with return on asset and return on investment. Finally, Firm size has a positive, very weak and insignificant moderating effect on the relationship between capital structure and financial performance of listed brewery companies in Nigeria. The study recommended amongst others that, there should be a review of the capital structure of the firms so as to ascertain the optimal capital structure that can be used to enhance financial performance, Equity position of the firms should be reviewed as well as this could have a way of increasing their performance in terms of return in investment if used adequately,  the size of the firm in terms of its total asset base should be considered by the management of the listed firms so that the right kind of capital structure for the company can be adopted.